On the nonlinear temperature dependence of residual stresses in solid oxide fuel cells. Issue 2 (3rd October 2020) - Lara‐Curzio, Edgar; Cakmak, Ercan; Lin, Lianshan; Marquez‐Rossy, Andres E.; Armstrong, Beth; Flores‐Betancourt, Alexis; Macias, Antonio
Abstract: The residual stresses in a dense yttria‐stabilized zirconia (YSZ) layer bonded to a porous NiO‐YSZ substrate were measured by X‐ray diffraction in air between 25°C and 900°C. It was found that the residual stresses on the outer surface of the YSZ layer were compressive, that their magnitude increased with decreasing temperature, and that the temperature dependence was nonlinear particularly at temperatures below 600°C. An elastic model that incorporates micromechanics and laminate theory was formulated to successfully predicts the nonlinearity of the temperature dependence of the residual stresses by accounting for the effect of the order‐disorder transition experienced by YSZ around 600°C and the magnetic transition of NiO at the Néel temperature around 265°C, on the properties of these materials. The implications of the results for the reliability of solid oxide fuel cells are discussed.